2021
DOI: 10.5435/jaaos-d-19-00866
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Valgus-Impacted and Nondisplaced Femoral Neck Fragility Fractures in the Elderly

Abstract: As the life expectancy of the worldwide population increases, the number of hip fractures in the elderly cohort is expected to grow. It is important for surgeons to critically analyze available treatment options for these injuries, with the goal of optimizing outcomes and minimizing complications. Femoral neck fractures make up approximately half of all hip fractures. Nonoperative treatment of valgus-impacted and nondisplaced (Garden I and II) femoral neck fractures has high rates of secondary displacement, os… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 41 publications
1
13
0
Order By: Relevance
“…However, more and more studies have reported that severe valgus‐impacted deformities are associated with a higher incidence of complications, such as ischemic necrosis and functional limitation 7,11,17,20 . Furthermore, posterior tilt of the femoral head, usually as a concomitant of the valgus‐impacted femoral neck fracture, is another high risk leading to poor outcomes 12,16,21,22 . As a result, restoration to the normal anatomy is important in valgus‐impacted femoral neck fracture, especially with severe posterior tilt.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, more and more studies have reported that severe valgus‐impacted deformities are associated with a higher incidence of complications, such as ischemic necrosis and functional limitation 7,11,17,20 . Furthermore, posterior tilt of the femoral head, usually as a concomitant of the valgus‐impacted femoral neck fracture, is another high risk leading to poor outcomes 12,16,21,22 . As a result, restoration to the normal anatomy is important in valgus‐impacted femoral neck fracture, especially with severe posterior tilt.…”
Section: Discussionmentioning
confidence: 99%
“… 7 , 11 , 17 , 20 Furthermore, posterior tilt of the femoral head, usually as a concomitant of the valgus‐impacted femoral neck fracture, is another high risk leading to poor outcomes. 12 , 16 , 21 , 22 As a result, restoration to the normal anatomy is important in valgus‐impacted femoral neck fracture, especially with severe posterior tilt.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with fragility fracture or posterior tilt greater than 20° have a high incidence of revision surgery when treated with IF. 40 42 When considering IF treatment, the surgeon should focus on the posterior tilt of the FNF and bone mineral density. Although there is a risk of femoral head necrosis with IF treatment, this approach offers the benefits of a biologically intact hip.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the middle-aged group and the young elderly group, these stable fractures of 31B1.1,31B1.2,31B2.1,31B2.2 and 31B3 occupy a certain proportion, about 1 / 3 of the whole group. Most of these types of fractures can get good treatment results when treated with IF.Doctors can give priority to preserving the original hip joint when treating elderly patients with these fracture types.Two studies have shown that patients with a posterior tilt of greater than 20° have a high rate of revision surgery when treated with IF and may bene t from primary arthroplasty (22,23).In the IF treatment of middle-aged and young elderly group, we should pay more attention to the posterior tilt of the proximal femoral neck. A 90-day reoperation rate was 9.4%, rate of conversion to THA was 6% and a 10-year reoperation rate was 34% and rate of conversion to THA was 14%, indicating that there is a substantial opportunity to improve the treatment of femoral neck fractures in the nongeriatric population (24,25).…”
Section: Discussionmentioning
confidence: 99%